157k views
0 votes
Which statement describes a process to solve square root b plus six minus square root b =5 Add a radical term to both sides and square both sides only once. Add a constant term to both sides and square both sides only once. Add a radical term to both sides and square both sides twice. Add a constant term to both sides and square both sides twice.

2 Answers

4 votes

Answer:

C

Explanation:

edg 2021

User Jigzat
by
4.9k points
6 votes

Answer:

Add a radical term to both sides and square both sides twice.

Explanation:

Given the radical equation

√(b+6) - √b = 5

We are to evaluate the expression for the value of b

Step 1: Add the radical term √b to both sides

√(b+6) - √b +√b = 5+√b

√(b+6) = 5+√b.

Step 2: Square both sides of the equation

(√(b+6))² = (5+√b.)²

b+6 = 25+10√b+ (√b)²

b+6 = 25+10√b + b

Step 3: collect like terms

b+6-b-25 = 10√b

-19 = 10√b

Step 4: square both sides of the resulting equation

(-19)² = (10√b)²

361 = 100b

b = 361/100

b = 3.61

Based on the calculation above, the correct option is C.

Add a radical term to both sides and square both sides twice.

User Victor Lee
by
4.4k points